2021
DOI: 10.3803/enm.2021.201
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in the Hospital

Abstract: Continuous glucose monitors (CGMs) have suddenly become part of routine care in many hospitals. The coronavirus disease 2019 (COVID-19) pandemic has necessitated the use of new technologies and new processes to care for hospitalized patients, including diabetes patients. The use of CGMs to automatically and remotely supplement or replace assisted monitoring of blood glucose by bedside nurses can decrease: the amount of necessary nursing exposure to COVID-19 patients with diabetes; the amount of time required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 83 publications
0
35
0
1
Order By: Relevance
“…Nevertheless, neither the pathophysiology nor the pathogenesis behind it has been fully understood, and only a few studies have demonstrated the detailed glycemic variability after pancreatectomy. CGM device provides us a utility tool for glucose monitoring (13,28). Recently, there were two studies using CGM to investigate patients' glycemic status and variation long after the original pancreatic surgery (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, neither the pathophysiology nor the pathogenesis behind it has been fully understood, and only a few studies have demonstrated the detailed glycemic variability after pancreatectomy. CGM device provides us a utility tool for glucose monitoring (13,28). Recently, there were two studies using CGM to investigate patients' glycemic status and variation long after the original pancreatic surgery (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals may use a variety of different diabetes technology options, including computerized insulin infusion calculators and, most recently, continuous glucose monitors (CGMs). 46,47 Diabetes care and education specialists should be involved with development and/or oversight of policies and procedures for the use, maintenance, and related practice issues based on regulatory requirements and device manufacturers’ specifications. 47…”
Section: Role Of the Diabetes Care And Education Specialist In The Ho...mentioning
confidence: 99%
“…46,47 Diabetes care and education specialists should be involved with development and/or oversight of policies and procedures for the use, maintenance, and related practice issues based on regulatory requirements and device manufacturers’ specifications. 47…”
Section: Role Of the Diabetes Care And Education Specialist In The Ho...mentioning
confidence: 99%
“…7 In addition, many hospital systems use color coding to monitor glycemic status to visually characterize the measured BG values. With increasing use of CGM data measured, for example, in the intensive care unit, 8 there is also a movement toward displaying their metrics in color. 5 Again, some hospitals choose colors consistent with the AGP color code and others do not.…”
Section: Editorialmentioning
confidence: 99%